(3GdHMQ GdQGFb TQM cfR GdObGFbs - (3GdeUQj GdMfaj, GHf fLje, Rjf GdOjf Hf EHQGgje Hf eMeO, (B970 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj OHQ GdCfGe HJOHjQg Gdbhj CeG HYO aEf CTQa GdYdhe hCYdGgG hChabgG hChaGgG Yde Gdabg hGdaJhi hCf cfR GdObGFb ddEeGe MGaX GdOjf GdfSaj CMSf eNJUQ Ufa aj abg GdCFeI GdMfajI hbO hVYhG dg TQhMG aCMHHJ Cf CVY dg TQMG jaUM Yf efWhbI hSejJg HGdHMQ GdQGFb TQM cfR GdObGFb s
(3BNQgG (B:s
(3HGH GdgOi eSGFd efKhQI hdh CPf dgG HYO eVj GdSfI cGf YdjgG YeQI eY GdML hdh MddgG aCMQeJ gcPG eQGQG Ke MLJ ef YGegG CLRCg Yf cd GdJMdjdGJ HJdc GdSfI GdhGMOI hdh de JML EdG ef bGHd cGf YdjgG Gdcd JMdjd YeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 64s
(3eYLe GdeDdajf (B1 / 740s
(3cTa GdXfhf (B2 / 1515s
(3TPQGJ GdPgH (B8 / 358s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs